ANALISIS HUBUNGAN ANTARA KEMACETAN DAN POLUSI UDARA DI JALAN SULTAN ABDURAHMAN PONTIANAK - Putra, Dedi Purwa; Sulandari, Eti; ., Said (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2016)
Exhaust Emission vehicle is one of the causes of air pollution in an area that is the impact of the use of vehicles as a means of transportation, be it land, sea or air. Any motor vehicle that uses the engine and oil as the driving source is the cause of the air pollution that comes from combustion imperfect issued in the form of exhaust emissions kendaraan.Memberikan description of the relationship of traffic on the roads in a region, the problems it causes, namely air pollution such as vehicle exhaust emissions in comparison to other areas in the city of Pontianak. Examines several types of air pollution caused by vehicle exhaust emissions which occurred on Jalan Sultan Abdurahman Pontianak. In this study used the method of observation, by analyzing the high percentage of the amount of emissions that occur in Jalan Sultan Abudrahman and analysis of vehicle exhaust emissions as sources and types of air pollutants, according existing emission standard and set. In this study during peak hours occur significant air pollution is at 32.88 NO2, SO2 amounted to 37.65, O3 for 1931 and Dust of 632. The density of vehicles influence of air pollution on roads Sultan Abdurahman, while the degree of saturation at peak hours of 0.46 at 12:15 to 13:15. The more dense then the vehicle will be high air pollution ditimbulkan.Tingkat exhaust emissions on the road during hours of peak Sultan Abdurahman is enormous NO2 mg / m³ of 32.88 g / m³, SO2 amounted to 37.65 g / m³, O3 at 1931 mg / m³ and Dust by 632 mg / m³. Keywords: Emissions, Air Pollution, and Congestion